Health-Related Quality of Life Assessment in Children and their Families: Aspects of Importance to the Pediatric Surgeon - Bloemeke, Janika; Witt, Stefanie; Bullinger, Monika; Dingemann, Jens; Dellenmark-Blom, Michaela; Quitmann, Julia (European Journal of Pediatric Surgery, 2020)
With the growing amount of chronic and rare diseases in childhood that often require lifelong treatment, improvement of health-related quality of life is a major goal in therapy. Therefore, the assessment of health-related quality of life from the patient's perspective as a relevant outcome parameter in clinical practice gained increased recognition. Health-related quality of life measures are still rarely applied in the pediatric practice context, although progress has been made in the development of instruments that are now ready for implementation. Inclusion of measures in research and practice is needed to accumulate and critically appraise knowledge about health-related quality of life to broaden the understanding of the child's health status, impacting on the whole family. From the perspective of a pediatric surgeon, knowledge about health-related quality of life of the children and their parents is important since it might influence treatment decisions and facilitates patient-physician communication. This article will review the concept of health-related quality of life, its methodological challenges and the application, and the challenges of health-related quality of life instruments in pediatric practice and health services research.
Keywords: health-related quality of life; pediatric surgery; pediatrics; patient-reported outcomes; children